Skin avulsion injuries caused by the application of adhesive drapes during total knee arthroplasty: A case report. Issue 24 (June 2018) - Yang, Bin; Xiong, Chuanzhi; Lu, Zhihua; Wang, Jingcheng
Abstract: Rationale: The use of adhesive drapes has decreased the incidence of surgical-site infections. Patient concerns: Despite the obvious benefits of the proper use of drapes, there remain many potential risks. Diagnose: A 66-year-old man with a history of left knee osteoarthritis and varus deformity underwent total knee arthroplasty at our hospital, upon removal of the adhesive drape by delicate peeling and warm saline lavage, a large area of the skin avulsion happened. Interventions: A standardized set of care measures were applied to the wound to avoid wound infection. Outcomes: After 6 weeks of treatment, the avulsed wound showed no signs of infection and had undergone re-epithelialization. Lessons: Individuals with high-risk skin avulsion injuries should be provided with preventive measures and the necessity of continuous application of adhesive drapes should be further studied.